Short-term androgen suppression and radiotherapy versus intermediate-term androgen suppression and radiotherapy, with or without zoledronic acid, in men with locally advanced prostate cancer (TROG 03.04 RADAR): 10-year results from a randomised, phase 3, factorial trial. Issue 2 (February 2019) - Denham, James W; Joseph, David; Lamb, David S; Spry, Nigel A; Duchesne, Gillian; Matthews, John; Atkinson, Chris; Tai, Keen-Hun; Christie, David; Kenny, Lizbeth; Turner, Sandra; Gogna, Nirdosh Kumar; et al.
Summary: Background: The optimal duration of androgen suppression for men with locally advanced prostate cancer receiving radiotherapy with curative intent is yet to be defined. Zoledronic acid is effective in preventing androgen suppression-induced bone loss, but its role in preventing castration-sensitive bone metastases in locally advanced prostate cancer is unclear. The RADAR trial assessed whether the addition of 12 months of adjuvant androgen suppression, 18 months of zoledronic acid, or both, can improve outcomes in men with locally advanced prostate cancer who receive 6 months of androgen suppression and prostatic radiotherapy. This report presents 10-year outcomes from this trial. Methods: For this randomised, phase 3, 2 × 2 factorial trial, eligible men were 18 years or older with locally advanced prostate cancer (either T2b-4, N0 M0 tumours or T2a, N0 M0 tumours provided Gleason score was ≥7 and baseline prostate-specific antigen [PSA] concentration was ≥10 μg/L). We randomly allocated participants in a 2 × 2 factorial design by computer-generated randomisation (using the minimisation technique, and stratified by centre, baseline PSA concentration, clinical tumour stage, Gleason score, and use of a brachytherapy boost) in a 1:1:1:1 ratio to four treatment groups. Patients in the control group received 6 months of neoadjuvant androgen suppression with leuprorelin (22·5 mg every 3 months, intramuscularly) and radiotherapy alone (short-term androgen suppression [STAS]); this treatment was either followed by another 12 months of adjuvant androgen suppression with leuprorelin (22·5 mg every 3 months, intramuscularly; intermediate-term androgen suppression [ITAS]), or accompanied by 18 months of zoledronic acid (4 mg every 3 months, intravenously) starting at randomisation (STAS plus zoledronic acid), or both (ITAS plus zoledronic acid). All patients received radiotherapy to the prostate and seminal vesicles, starting from the end of the fifth month of androgen suppression; dosing options were 66, 70, and 74 Gy in 2-Gy fractions per day, or 46 Gy in 2-Gy fractions followed by a high-dose-rate brachytherapy boost dose of 19·5 Gy in 6·5-Gy fractions. Treatment allocation was open label. The primary endpoint was prostate cancer-specific mortality and was analysed according to intention-to-treat using competing-risks methods. The trial is closed to follow-up and this is the final report of the main endpoints. This trial is registered withClinicalTrials.gov, numberNCT00193856 . Findings: Between Oct 20, 2003, and Aug 15, 2007, 1071 men were enrolled and randomly assigned to STAS (n=268), ITAS (n=268), STAS plus zoledronic acid (n=268), and ITAS plus zoledronic acid (n=267). Median follow-up was 10·4 years (IQR 7·9–11·7). At this 10-year follow-up, no interactions were observed between androgen suppression and zoledronic acid so the treatment groups were collapsed to compare treatments according to duration of androgen suppression: 6 months of androgen suppression plus radiotherapy (6AS+RT) versus 18 months of androgen suppression plus radiotherapy (18AS+RT) and to compare treatments according to whether or not patients received zoledronic acid. The total number of deaths was 375 (200 men receiving 6AS+RT and 175 men receiving 18AS+RT), of which 143 (38%) were attributable to prostate cancer (81 men receiving 6AS+RT and 62 men receiving 18AS+RT). When analysed by duration of androgen suppression, the adjusted cumulative incidence of prostate cancer-specific mortality was 13·3% (95% CI 10·3–16·0) for 6AS+RT versus 9·7% (7·3–12·0) for 18AS+RT, representing an absolute difference of 3·7% (95% CI 0·3–7·1; sub-hazard ratio [sHR] 0·70 [95% CI 0·50–0·98], adjusted p=0·035). The addition of zoledronic acid did not affect prostate cancer-specific mortality; the adjusted cumulative incidence of prostate cancer-specific mortality was 11·2% (95% CI 8·7–13·7) with zoledronic acid vs 11·7% (9·2–14·1) without, representing an absolute difference of −0·5% (95% CI −3·8 to 2·9; sHR 0·95 [95% CI 0·69–1·32], adjusted p=0·78). Although safety analysis was not prespecified for this 10-year analysis, one new serious adverse event (osteonecrosis of the mandible, in a patient who received 18 months of androgen suppression plus zoledronic acid) occurred since our previous report, bringing the total number of cases of this serious adverse event to three (<1% out of 530 patients who received zoledronic acid evaluated for safety) and the total number of drug-related serious adverse events to 12 (1% out of all 1065 patients evaluable for safety). No treatment-related deaths occurred during the study. Interpretation: 18 months of androgen suppression plus radiotherapy is a more effective treatment option for locally advanced prostate cancer than 6 months of androgen suppression plus radiotherapy, but the addition of zoledronic acid to this treatment regimen is not beneficial. Evidence from the RADAR and French Canadian Prostate Cancer Study IV trials suggests that 18 months of androgen suppression with moderate radiation dose escalation is an effective but more tolerable option than longer durations of androgen suppression for men with locally advanced prostate cancer including intermediate and high risk elements. Funding: National Health and Medical Research Council of Australia, Novartis Pharmaceuticals Australia, AbbVie Pharmaceuticals Australia, New Zealand Health Research Council, New Zealand Cancer Society, Cancer Standards Institute New Zealand, University of Newcastle (Australia), Hunter Medical Research Institute, Calvary Mater Newcastle Radiation Oncology Fund, and Maitland Cancer Appeal.